2009
DOI: 10.1590/s1413-41522009000300012
|View full text |Cite
|
Sign up to set email alerts
|

A influência das atividades mineradoras na alteração do pH e da alcalinidade em águas fluviais: o exemplo do rio Capivari, região do carste paranaense

Abstract: A influência das atividades mineradoras na alteração do pH e da alcalinidade em águas fluviais: o exemplo do rio Capivari, região do carste paranaense AbstractMining activities causes many kinds of environmental impacts over environment. In this paper we describe the research developed in the Capivari watershed, in the Curitiba metropolitan region, Paraná, Brazil. Alkalinity and pH changes in Capivari stream over 12 years were observed. The sampling program was performed in 387 sampling day's series at 1986/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
1
6
0
7
Order By: Relevance
“…Fritzsons et al (2009) says that to evaluate the characteristics of surface waters of these rivers, warn that the high values of pH may be related to the limestone mining activities in these watersheds and highlight the existence of pumping water from the pits deposits, the river bed Bacaetava. But in this case, as seen in the survey of land use in the watersheds are limestone-mining activity downstream of the stations (MSCD1 and MSCD2) and shows that the results are related to geological domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fritzsons et al (2009) says that to evaluate the characteristics of surface waters of these rivers, warn that the high values of pH may be related to the limestone mining activities in these watersheds and highlight the existence of pumping water from the pits deposits, the river bed Bacaetava. But in this case, as seen in the survey of land use in the watersheds are limestone-mining activity downstream of the stations (MSCD1 and MSCD2) and shows that the results are related to geological domain.…”
Section: Resultsmentioning
confidence: 99%
“…To Fiori (1993), Capiru formation Precambrian age encompasses all metasediments Acungui Group, including a track with reddish phyllites, with interbedded quartzites not very frequent; one with marble and / or metalimestones and their intercalation of phyllites and quartzites; and another track with switching banks or layers of quartzite, phyllites and marbles, with thicknesses in the range of hundreds of meters GUARDA, 2008). Phyllites and marbles are generally banded or rhythmic and more homogeneous quartzite.…”
Section: Characterization Of Local Geologymentioning
confidence: 99%
“…Tal ocorrência pode interferir nos valores de alcalinidade, tornando-a, uma importante variável de avaliação hídrica. Por outro lado, Fritzsons et al (2009) mencionam que águas de baixa alcalinidade (<24 mg.L -1 como CaCO3) apresentam baixa capacidade de tamponamento e, assim, são suscetíveis às mudanças de pH.…”
Section: Caracterização Da Qualidade Da áGuaunclassified
“…In the study by Scheffer [70] found 133 mg x L -1 CaCO 3 for the same environment. It should be noted that Fritzsons [71] states that the alkalinity in most Brazilian rivers is between 30 and 500 mg x L -1 CaCO 3 .…”
Section: Determination Of Total Alkalinity Nutrients and Chlorophyllmentioning
confidence: 99%